2015
DOI: 10.1097/ccm.0000000000001192
|View full text |Cite
|
Sign up to set email alerts
|

Delayed Emergency Team Calls and Associated Hospital Mortality

Abstract: Among ward patients, emergency team activation in response to acute deterioration triggered more than 15 minutes after detection and documentation of instability is independently associated with an increased risk of ICU admission and death.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
77
2
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 78 publications
(84 citation statements)
references
References 19 publications
(35 reference statements)
4
77
2
1
Order By: Relevance
“…In this light, in a recent issue of Critical Care Medicine, the study by Barwise et al (7), which found a significant relationship between delayed RRT activation and increased hospital mortality and morbidity as well as increased length of stay in a tertiary care hospital, is important in helping our understanding of the effectiveness and implementation of a RRS: 1) these findings are consistent with other similar studies (8)(9)(10)(11)(12)) that all showed a significant relationship between delayed calls and increased hospital mortality (it was estimated that every 100 delayed calls were associated with an extra 13 deaths by a multicenter study) (12); 2) the consistency and robustness of such findings across different studies conducted at different settings provided pivotal evidence that nondelayed RRT activation could save more patient lives and support the notion that a RRS actually can save patient lives; 3) the rate of delayed calls in the current study is high (57%, in comparison with 29% reported in a large multicenter study which was based on a more relaxed delay call definition [> 15 min given the exist calling criteria (12) compared with the current study of using > 1 hr as the cutoff]); 4) the substantial proportion of delayed calls highlighted that despite the promises, much more could be done to improve the compliance of RRTs and RRSs to save patient lives; 5) the study included a large number of RRT calls (1,227) in 2012 in an institution with an RRS since 2007. It is especially important to recognize that delayed calls to a RRT not only occurred in a hospital with a newly implemented RRS.…”
supporting
confidence: 79%
“…In this light, in a recent issue of Critical Care Medicine, the study by Barwise et al (7), which found a significant relationship between delayed RRT activation and increased hospital mortality and morbidity as well as increased length of stay in a tertiary care hospital, is important in helping our understanding of the effectiveness and implementation of a RRS: 1) these findings are consistent with other similar studies (8)(9)(10)(11)(12)) that all showed a significant relationship between delayed calls and increased hospital mortality (it was estimated that every 100 delayed calls were associated with an extra 13 deaths by a multicenter study) (12); 2) the consistency and robustness of such findings across different studies conducted at different settings provided pivotal evidence that nondelayed RRT activation could save more patient lives and support the notion that a RRS actually can save patient lives; 3) the rate of delayed calls in the current study is high (57%, in comparison with 29% reported in a large multicenter study which was based on a more relaxed delay call definition [> 15 min given the exist calling criteria (12) compared with the current study of using > 1 hr as the cutoff]); 4) the substantial proportion of delayed calls highlighted that despite the promises, much more could be done to improve the compliance of RRTs and RRSs to save patient lives; 5) the study included a large number of RRT calls (1,227) in 2012 in an institution with an RRS since 2007. It is especially important to recognize that delayed calls to a RRT not only occurred in a hospital with a newly implemented RRS.…”
supporting
confidence: 79%
“…Where call-out times and the time taken to initiate measures exceed 15 minutes, a poorer prognosis may be expected (22). Our survey showed that MICNs had a median call-out time of 5 minutes.…”
Section: Reduced Mortality?mentioning
confidence: 97%
“…In Table 2, the articles showed that delayed RRT activations are associated with increased hospital mortality rates, length of hospital stay, number of CRAs, and higher risk of admission to ICU. (8)(9)(10)(11) For patients admitted to ICU there is also increased mechanical ventilation time, length of hospital stay, and death. (9) There was no reduction of delayed activation even with monitoring of patients.…”
Section: Full Text N=26 Excluded N=7mentioning
confidence: 99%